2022
DOI: 10.1038/s41598-022-09512-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of vertebrate mitochondrial reveals a differential of rearrangements rate between taxonomic class

Abstract: Vertebrate mitochondrial genomes have been extensively studied for genetic and evolutionary purposes, these are normally believed to be extremely conserved, however, different cases of gene rearrangements have been reported. To verify the level of rearrangement and the mitogenome evolution, we performed a comparative genomic analysis of the 2831 vertebrate mitochondrial genomes representing 12 classes available in the NCBI database. Using a combination of bioinformatics methods, we determined there is a high n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…Gene arrangement comparison is an important tool for resolving deep-level phylogenetic relationships [ 97 , 98 ]. Genome rearrangement analysis is a routine analysis in comparative mitochondrial genomics [ 33 , 72 , 73 , 99 , 100 , 101 ]. Regarding the Ixodidae mitogenomes, Black and Roehrdanz first reported two gene arrangement types [ 102 ], and Shao et al further summed up three types [ 59 ], which were confirmed by another study [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gene arrangement comparison is an important tool for resolving deep-level phylogenetic relationships [ 97 , 98 ]. Genome rearrangement analysis is a routine analysis in comparative mitochondrial genomics [ 33 , 72 , 73 , 99 , 100 , 101 ]. Regarding the Ixodidae mitogenomes, Black and Roehrdanz first reported two gene arrangement types [ 102 ], and Shao et al further summed up three types [ 59 ], which were confirmed by another study [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genomic architecture is probably the most fruitful Genome-level character, with new findings including two co-existing and divergent mt-molecules in single individuals in vertebrate [2] and invertebrates [3], changes in the transcriptional orientations of genes [2], architectural variation of individual genes [4], etc.. Recent meta-analysis [5,6] reinforced more variable rearrangements than anticipated, and identified convergence events. However, as taxonomy experience shows, evolution patterns differ along ranks [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Older methods can produce inaccuracies due to the amplification of nuclear mitochondrial DNA segments (NUMTs), the variation of sequences at primer bonding sites and changes in gene structure (Mueller & Boore, 2005; Cameron, 2014; Parakatselaki et al, 2022). On the other hand, mitogenomes still present challenges that only LRS can overcome, such as accurately capturing gene arrangements, long TRs and long duplications (Konrad et al, 2017; Torres et al, 2019; Zardoya, 2020; Montaña-Lozano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%